The influence of Muzakki loyalty, equitable zakat distribution and amil competency on the increase in the number of Muzakki at Lembaga Zakat Negeri Kedah - Diana, Aan (2025)
This study aims to analyze the influence of Muzakki loyalty, fair zakat distribution, and amil competence on increasing the number of Muzakki in Lembaga Zakat Negeri Kedah (LZNK). Zakat is one of the important pillars in Islamic teachings that has a strategic role in creating socio-economic welfare, and its effective management can increase in the number of participating Muzakki. This study used a quantitative approach with a survey method of Muzakki registered in LZNK. The analysis shows a significant relationship between Muzakki loyalty and increasing the number of Muzakki, as well as between fair distribution of zakat and increasing the number of Muzakki. In addition, the competency of amil zakat has also been proven to play an important role in increasing the trust of Muzakki towards zakat institutions, which in turn has an impact on increasing the number of Muzakki. These results emphasize the importance of strategic management practices in zakat institutions, which encourage transparency, accountability, and amil skill development to ensure fair and efficient zakat distribution